The Quaternary coversands of southwest France. (15th September 2015) - Sitzia, Luca; Bertran, Pascal; Bahain, Jean-Jacques; Bateman, Mark D.; Hernandez, Marion; Garon, Henri; de Lafontaine, Guillaume; Mercier, Norbert; Leroyer, Chantal; Queffelec, Alain; Voinchet, Pierre
Abstract: Detailed stratigraphic analysis and numerical dating (OSL, IRSL, ESR, 14C) of Pleistocene coversands in southwest France enable the construction of a renewed chronostratigraphic framework for sand deposition. The chronological data obtained from sandsheet units testify to the development of transgressive dunefields since at least the Middle Pleistocene (MIS 10). Three main phases of accumulation occurred during the Last Glacial. The oldest one (64–42 ka) is associated with wet sandsheet facies, histic horizons and zibar-type dune fields, which reflect deposition in a context strongly influenced by the groundwater table. The Late Pleniglacial (24–14 ka) corresponds to the main phase of coversand extension in a drier context. Silty gley horizons suggest, however, local interruptions of sand drifting during GS 2.1. Lateglacial stabilization of the coversands may not have occurred before GI-1c (Allerød), which was typified by the development of cumulic arenosols. These were covered by parabolic dunes during the Younger Dryas. The variations in extent of the emerged continental shelf during the glacial–interglacial cycles may explain the uneven geographical distribution of sand deposition through time. Because of coastline retreat up to 100 km north of 45°N during the LGM lowstand, the coversands were unable to reach the northern part of the basin. Comparison with other European regions highlights stronger affinities of the French record with Portugal than with the Netherlands and Great Britain, probably because of reduced influence of permafrost. Highlights: Renewed chronostratigraphic framework for coversands in southwest France. Transgressive dunefields developed since the Middle Pleistocene (MIS 10). Wet sandsheets (SS) dominate at 64–42 ka, dry SS at 24–14 ka, and slipface dunes at 12 ka. Coastline retreat during glacials explains the spatial distribution of coversands. Permafrost explains the contrasting coversand records in SW and NW Europe.